The Young Innovators Program at the Eshelman Institute for Innovation: a case study examining the role of a professional pharmacy school in enhancing STEM pursuits among secondary school students - Adam D. Friedman; Carlos R. Melendez; Antonio A. Bush; Samuel K. Lai; Jacqueline E. McLaughlin (SpringerOpen, 2017)
Abstract Background Professional schools, such as schools of pharmacy, are rarely involved with promoting STEM interests among secondary school students. To address this shortcoming, the Young Innovators﻿ Program (YIP) was created to provide local secondary school students a summer immersive experiential program at the UNC Eshelman School of Pharmacy. The objective of this study was to assess the ability of the inaugural YIP to promote STEM interest, career awareness, and self-efficacy. Results YIP interns maintained high levels of STEM interest, career awareness, and self-efficacy. In addition, they reported significant increases in their perceptions of having role models in science. Conclusions Immersion in research laboratories and clinics at a school of pharmacy can promote high levels of STEM interest, career awareness, and self-efficacy and provide interns with STEM professional role models. Our findings support YIP's vision that professional pharmacy schools can play an influential role in recruiting secondary school students to STEM disciplines.